Comprehending The Beatles Through its Song ‘Yellow Submarine’: Critical Discourse Analysis - Manshur, Fadlil Munawwar; Faruk, Faruk; Mahmudah, Mahmudah (Universitas Negeri Medan, 2024)
This study aims to elaborate on The Beatles band through a study of one of its songs called Yellow Submarine. This study uses the Critical Discourse Analysis (CDA) approach, an approach that aims to describe, interpret, and critically explain in a qualitative manner about how discourse builds, maintains, and legitimizes social inequalities. A number of relevant primary and secondary literatures were studied and analyzed critically to understand and recognize the process of creating, producing, broadcasting, concert performance, and public reception for the song Yellow Submarine by the Beatles and its socio-cultural context. The results of the study showed that this song was dedicated to children who lost the joy and delight of their childhood due to ideological conflicts (capitalism-communism), social tensions, the Vietnam War, the Cold War, drugs, etc., in the 1960s. Although this song has been associated with various interpretations, ranging from drugs, money, war, peace, cowardice to death, most of The Beatles’ fans and observers believe there is an element of joy and delight that they would like to present to their children. They gave joy and delight, especially to children, when the state failed to provide them.